PROCESS AND PRACTICE OF ACADEMIC WRITING AT TANZANIAN HIGHER LEARNING INSTITUTION - Urassa, Bariki Johanson (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
This study investigated students’ perceptions of academic writing in higher learning institutions: process and practices with a mixed-methods approach to explore how students in higher learning institutions perceive academic writing, their writing process, and practices that they underwent to achieve the literacies at the higher learning context. The research combined quantitative data from surveys to capture trends in students’ perceptions of the writing process and practices, qualitative data from focus group interviews and documentaries from bachelor students at the Institute of Finance Management in Tanzania. The academic literacy framework informed the design and interpretation of both datasets, emphasizing how students’ writing practices were linked to broader issues of power, identity, and access within academic settings. The findings showed students processed and practiced writing with challenges in plagiarism, citation and referencing awareness, lack of constructive writing feedback from lecturers, and mechanics issues in writing that result in producing texts below the required standards. Results further revealed that access to online materials and more practice in real writing as the factors that can support improving academic writing. At the same time, the English language background was the main factor that hindered academic writing practices.